Flower-like MoS2 nanocrystals: a powerful sorbent of Li+ in the Spiro-OMeTAD layer for highly efficient and stable perovskite solar cells. Issue 8 (30th January 2019) - Jiang, Lu-Lu; Wang, Zhao-Kui; Li, Meng; Li, Chun-He; Fang, Peng-Fei; Liao, Liang-Sheng
Abstract : A powerful sorbent of Li +, flower-like MoS2 nanocrystals, was doped into the Spiro-OMeTAD layer for highly efficient and stable perovskite solar cells. Abstract : 2, 2, 7, 7-Tetrakis-( N, N -di- p -methoxyphenylamine)9, 9-bifluorene (Spiro-OMeTAD) is a widely employed hole-transporting layer (HTL) in typical n-i-p structure perovskite solar cells (PSCs). And the p-type dopants of bis(trifluoromethane)sulfonimide lithium salt (Li-TFSI) and tert -butylpyridine ( t BP) have to be utilized to improve the hole mobility and film conductivity of Spiro-OMeTAD. However, the incorporation of these additives will cause the issue of deliquescence, strongly speeding up the degradation of the Spiro-OMeTAD layer and thus of the perovskite layer. Herein, we developed a modified Spiro-OMeTAD layer using MoS2 with the 2H semiconducting phase and flower-like microstructure. The addition of MoS2 played an important role in improving the hole mobility and enhancing the film stability of Spiro-OMeTAD. The resulting PSCs based on the MoS2 -modified Spiro-OMeTAD HTL delivered a champion power conversion efficiency as high as 20.18%. More importantly, the incorporation of MoS2 could suppress the Li + migration in the HTL owing to the strong adsorption ability and large specific surface area of flower-like MoS2 nanoparticles. As a result, the fabricated PSC without encapsulation exhibited promising stability by retaining almost 85% of the initial PCE even after 300 h exposure to air while the reference device only retained about 30% of its initial PCE.